PROSES PENGUATAN KARAKTER PERCAYA DIRI PADA SISWA MELALUI METODE DISKUSI TANYA JAWAB PADA PEMBELAJARAN TEMATIK KELAS IV DI SDN CILAKU - Yunanto, Abdul Karim Zuhartri; Jamaludin, Ujang; Hakim, Zerri Rahman (ATTA`DIB, 2020)
This research aims to find out the procces of strengthening the character of confidience in students through the method of question and answer discussion. The data collection process in this study is focused on 1) teacher planning before carrying out learning activities 2) the process of implementing learning activities 3) discussion learning evaluation activities in the process of strengthening confident character in students through question and answer discussion methods. In the process of developing a confident charcter in student many challenges faced given the difficulty of strengthening this confident character then the involvement of various parties such as parents is mandatory that spend a lot of time with students. But students also need to be given a special character education that should be obtained in the school environment through regular learning activities. This research uses a qualitative descriptive research method that is a research method that aims to describe phenomena that occur objectively. The results show holistically that learning activities through this question and answer discussion method provide good benefits for school and students, especially because this question and answer method is able to provide stimulus so that students can be more confident, able to communicate, can work together, tolerate each other, like to read and share various other, like to read and share various other characters.